2011
DOI: 10.3390/rel2020145
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Grief in the Aftermath of Homicide: Spiritual Crisis and Distress in an African American Sample

Abstract: Both grieving the loss of a loved one and using spirituality or religion as an aid in doing so are common behaviors in the wake of death. This longitudinal examination of 46 African American homicide survivors follows up on our earlier study that established the relation between positive and negative religious coping on the one hand and complicated grief (CG) on the other. In the current report, we broadened this focus to determine the relation between religious coping and other bereavement outcomes, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 60 publications
3
21
0
1
Order By: Relevance
“…Still, this explanation alone is insufficient, as CSG scores in our sample were equally skewed, and yet were robust in their association with difficulty making meaning of the loss. Notably, our results are congruent with our previous findings [26], where we observed that CSG but not PRC was associated with CG; and, similarly, that PRC was not associated with PTSD or depression [62].…”
Section: Complicated Spiritual Grief and Meaning Making In A Diverse supporting
confidence: 83%
See 3 more Smart Citations
“…Still, this explanation alone is insufficient, as CSG scores in our sample were equally skewed, and yet were robust in their association with difficulty making meaning of the loss. Notably, our results are congruent with our previous findings [26], where we observed that CSG but not PRC was associated with CG; and, similarly, that PRC was not associated with PTSD or depression [62].…”
Section: Complicated Spiritual Grief and Meaning Making In A Diverse supporting
confidence: 83%
“…Consistent with previous studies [26,62,65], we found that two forms of spiritual responses, PRC and CSG-one characteristically considered positive and one negative-related quite differently to bereavement outcome. On the one hand, in this study, use of religion as a positive resource in coping proved unrelated to adjustment to loss, whereas maladaptive religious coping was consistently related to elevated grief, replicating our previous findings [26] with a sample of homicide survivors.…”
Section: Complicated Spiritual Grief and Complicated Grief: Comparingsupporting
confidence: 81%
See 2 more Smart Citations
“…In the context of bereavement, prolonged and debilitating spiritual distress of this sort, which includes the collapse or erosion of the griever's sense of relationship to God and/or their faith community, has been termed complicated spiritual grief (CSG) [8,9] and has shown an empirically consistent association with CG [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%